Informal Cape Verdean settlement in Lisbon: Bairro 6 de Maio and the challenge for urban planning - Tarsi, Elena (2017)
Bairro 6 de Maio was built by immigrants from Cape Verde, a former Portuguese colony, in the 1970s and 1980s. It was one of the many informal settlements in the suburbs of Lisbon and is one of the last neighbourhoods left "alive" after the 1993 PER Program demolished most of the spontaneous settlements and relocated their population to public housing. In recent years, the Municipality of Amadora, where Bairro 6 de Maio is located, has begun knocking down houses again under the auspices of the over 20-year-old PER, without creating real alternatives for the displaced population. Based on a critical analysis of this case study, this paper indicates the need for socially sustainable policies and programmes regarding informal settlements in Portugal and other European countries. It proposes a different and challenging approach to planning that is not based on legal rhetoric but comes from both defending people's fundamental right to housing and having a multicultural vision of cities.